The end of application of international humanitarian law - Milanovic, Marko (Cambridge University Press, 2014)
This article provides a systematic overview of the rules governing the end of application of international humanitarian law, or the law of armed conflict. It articulates the general principle that unless there is a good reason of text, principle or policy that warrants an exception, the application of IHL will cease once the conditions that triggered its application in the first place are no longer met. For IHL to apply, its distinct thresholds of application – international armed conflict, belligerent occupation, and non-international armed conflict – must continue to be satisfied at any given point in time. The article also examines situations in which a departure from the general rule is warranted, as well as the factors that need to be taken into account in determining the end of each type of armed conflict. In doing so, the article analyzes terminating processes and events, which generally end the application of IHL (but not necessarily all of it), and transformative processes and events, which end the application of one IHL sub-regime but immediately engage another. Finally, the article briefly looks at the (putative) armed conflict between the US and Al-Qaeda and its seemingly imminent end.